Improvement Efforts Of Indonesia's Defense Diplomacy Performance Via Deterrence Strategy In Dealing North Natuna Sea Conflict (2016-2021) - Binsar Simorangkir; Tri Legionosuko; Surryanto Djoko Waluyo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
One of Indonesia's most actual maritime border disputes is the border dispute between Indonesia and China in the North Natuna Sea. This research focuses this on examining how to improve the performance of Indonesia's defense diplomacy through deterrence strategies in dealing with conflicts in the North Natuna Sea. This research uses qualitative-descriptive. The location of this research was carried out in Jakarta, in this case the Ministry of Defense of the Republic of Indonesia. Research time for six months. The research subjects were six sources. The object of this research is about improving the performance of defense diplomacy through deterrence strategies in the North Natuna Sea. The primary data collection technique is an in-depth interview method, while the secondary data collection technique uses a literature study. The results show that the performance of Indonesia's defense diplomacy in the North Natuna Sea for the 2016-2021 period is still relatively weak, especially if it is related to the potential threat from the Chinese side. Indonesia's deterrence strategy in the North Natuna Sea for the 2016-2021 period has so far been carried out with external policies, namely cooperating with foreign parties, both bilaterally, regionally, and globally. Indonesia's efforts to improve defense diplomacy in the North Natuna Sea through a deterrence strategy can be carried out with at least 10 items of deterrence strategy, including conducting joint military exercises; enhance joint surveillance and patrols; increase the discussion of maritime issues in regional and international forums; and increase advocacy for the law of the sea.